2012
DOI: 10.1371/journal.pntd.0001700
|View full text |Cite
|
Sign up to set email alerts
|

First Molecular Epidemiological Study of Cutaneous Leishmaniasis in Libya

Abstract: BackgroundCutaneous leishmaniasis (CL) is a major public health problem in Libya. The objective of this study was to investigate, for the first time, epidemiological features of CL outbreaks in Libya including molecular identification of parasites, the geographical distribution of cases and possible scenarios of parasite transmission.Methodology/Principal FindingsWe studied 450 patients that came from 49 areas distributed in 12 districts in north-west Libya. The patients' ages ranged from 9 months to 87 years … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
46
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(55 citation statements)
references
References 32 publications
9
46
0
Order By: Relevance
“…In the present study, approximately 87% of the wounds exist on the hands, face, and neck because of sleeping in the outdoor, without the use of linen and lace, and lack of proper body cover in summer, considering the high prevalence of the disease in tropical regions, while in Brazil more than 34% of wounds occurred in the legs, given the type of wearing clothing among Brazilians (25). Other studies have also shown a higher frequency of the disease in men (23,30). In our study, 55% of the cases were men.…”
Section: Discussionsupporting
confidence: 69%
“…In the present study, approximately 87% of the wounds exist on the hands, face, and neck because of sleeping in the outdoor, without the use of linen and lace, and lack of proper body cover in summer, considering the high prevalence of the disease in tropical regions, while in Brazil more than 34% of wounds occurred in the legs, given the type of wearing clothing among Brazilians (25). Other studies have also shown a higher frequency of the disease in men (23,30). In our study, 55% of the cases were men.…”
Section: Discussionsupporting
confidence: 69%
“…Therefore, failure to observe amastigotes does not exclude a diagnosis of CL and such infection in endemic areas may be diagnosed on the basis of their clinical features as leishmaniasis. 4,9,20 Mohammed had claimed that amastigotes at certain time of the disease are impossible to be detected. 24 The disappearance of such cells infected with the amastigote form in spite of the disease process is still continuous delineate that these phagocytes, giant cells, macrophages and monocytes, at specific point of the disease process become resistant to be infected with the amastigotes.…”
Section: Al-khayat Zay Et Al Int J Res Dermatol 2018 Mar;4(1):1-7mentioning
confidence: 99%
“…2,3 Leishmania has two stages in their life cycle: the intracellular amstigote form within macrophages of vertebrates and promastigote stage in the gut of invertebrate host. 4 In endemic and developing countries such as Iraq in which such laboratory facilities like ELISA kits or PCR technique is not routinely available in such district health centers so the diagnosis is mainly dependent on the clinical features of the lesion in addition to the staining a smear from the lesion by Giemsa stain.…”
Section: Introductionmentioning
confidence: 99%
“…Several PCR approaches have been published based on different target genes, i.e., the cysteine protease B (cpb) [14], the cytochrome b (cyt b) [15], the internal transcribed spacer 1 (ITS1) region of the small subunit ribosomal RNA (SSU-rRNA) gene [16], the glucose-6-phosphate dehydrogenase (G6PD) [17], the heat shock protein 70 (hsp70) [18], the spliced leader mini-exon [19], the SSU-rRNA gene [20] and the triose-phosphate isomerase (tim) genes [21]. Of these, the ITS1 region of the SSU-rRNA gene has been one of the common genetic markers used to detect Leishmania species in the Old World [13,16,[22][23][24].…”
Section: Introductionmentioning
confidence: 99%